2010
DOI: 10.1007/s00540-010-0871-z
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal fluid leakage in benchtop trials: comparison of static versus dynamic ventilation model with and without lubrication

Abstract: Purpose Longitudinal folds in tracheal tube (TT) cuffs cause leakage of pooled secretions past the tube cuff, and the most common in vitro method to test the efficacy of a new tube is a benchtop model using an artificial rigid trachea. This study compared the potential of a static and dynamic ventilation benchtop model and cuff lubrication in testing the tracheal sealing properties of a given TT cuff. Methods Static trial Six brands of 7.5 mm internal diameter (ID) cuffed TT (n = 8) with high volume-low pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
1
20
1
1
Order By: Relevance
“…This in vitro test does not attempt to simulate the complexity of the physiological conditions: the stiff cylindrical PVC trachea, the vertical position, and the dyed-water viscosity may all favor leakage across the cuff; nevertheless, this setting, which with some simplification could be used in every anesthesia department to form a proper opinion on the quality of a particular ETT, is the common in vitro method to test the efficacy of new ETT cuffs in preventing fluid leakage [9]. The cuff-sealing properties reported in several studies with these settings were recently confirmed in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…This in vitro test does not attempt to simulate the complexity of the physiological conditions: the stiff cylindrical PVC trachea, the vertical position, and the dyed-water viscosity may all favor leakage across the cuff; nevertheless, this setting, which with some simplification could be used in every anesthesia department to form a proper opinion on the quality of a particular ETT, is the common in vitro method to test the efficacy of new ETT cuffs in preventing fluid leakage [9]. The cuff-sealing properties reported in several studies with these settings were recently confirmed in human studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the seal between the cuff and the moist tracheal mucosa might actually be better, especially with the use of lubricant at the time of intubation. 4,11,12 The upward sweeping movement of the ciliated mucosa might also decrease aspiration. Furthermore, subglottic collections are more viscous than water, and their volume is not likely to be as high as 20 mL.…”
Section: Discussionmentioning
confidence: 99%
“…47, 48 Blunt and colleagues 47 placed dye in the subglottic space and observed for leakage into the tracheobronchial tree in 2 different studies. In their in vitro model, leakage was 0% for cuffs treated with water-soluble gel and 100% for non-treated cuffs.…”
Section: Methodsmentioning
confidence: 99%